Técnica del aula taller para el proceso de enseñanza – aprendizaje de los saberes ancestrales alimentarios - Chango Pila, Jessica Elizabeth (2020)
Ancestral knowledge is knowledge that is a legacy of people as part of their cultural identity, which is why the research identified the problem of lack of knowledge about ancestral food knowledge among students in the seventh year of basic general education at the "Marco Aurelio Subía Martínez - Battle of Panupali" Educational Unit. For this reason, the objective of the research was to strengthen the teachinglearning process related to ancestral food knowledge by applying the classroomworkshop technique. The methodology used was characterized by the qualitative approach, action research, bibliographic and field research, the inductive method and the technique of observation with the observation card as an instrument aimed at students. The contribution of the research was practical because with the application of the active technique and the didactic resource, the teaching-learning process related to the ancestral food knowledge was strengthened; developing the collective participation, the team work, the motivation for the topic and the interest for the didactic resource, giving as a result the recognition and the valuation of the ancestral knowledge. In this way, it became evident that the classroom-workshop technique is ideal for the teaching-learning process because the students with solvency recognized the ancestral food knowledge of the area as part of their identity. Thus, it allows teachers to use this pedagogical alternative as a learning tool, based on the reality lived by the inhabitants of the Tanicuchi parish